2016
DOI: 10.1080/21505594.2016.1257458
|View full text |Cite
|
Sign up to set email alerts
|

The microbiome-metabolome crosstalk in the pathogenesis of respiratory fungal diseases

Abstract: Filamentous fungi of the genus Aspergillus are responsible for several superficial and invasive infections and allergic syndromes. The risk of infection and its clinical outcome vary significantly even among patients with similar predisposing clinical factors and pathogen exposure. There is increasing evidence that the individual microbiome supervises the outcome of the host-fungus interaction by influencing mechanisms of immune regulation, inflammation, metabolism, and other physiological processes. Microbiom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 113 publications
0
20
0
Order By: Relevance
“…As suggested by the Human Microbiome Project, in the future, it will be necessary to study oral, skin, and airway microbiota in HSCT to improve the understanding of the correlation between the different microbiotas and their role in the development of the main complications of HSCT. [122][123][124]137 In addition, thanks to next-generation DNA sequencing, metabolomics and the utilization of gnotobiotic models, it has been possible to dissect compositional and functional microbiome structures, as well as infer the mechanisms underlying the role of the microbiome in human biology. The study of microbial genes and metabolic pathways with newer methods, such as shotgun metagenomic sequencing, metabolomics, and metaproteomics, will further elucidate the mechanism of interaction between the GM and the host, expanding it beyond bacterial taxonomy.…”
Section: Conclusion and Future Strategiesmentioning
confidence: 99%
“…As suggested by the Human Microbiome Project, in the future, it will be necessary to study oral, skin, and airway microbiota in HSCT to improve the understanding of the correlation between the different microbiotas and their role in the development of the main complications of HSCT. [122][123][124]137 In addition, thanks to next-generation DNA sequencing, metabolomics and the utilization of gnotobiotic models, it has been possible to dissect compositional and functional microbiome structures, as well as infer the mechanisms underlying the role of the microbiome in human biology. The study of microbial genes and metabolic pathways with newer methods, such as shotgun metagenomic sequencing, metabolomics, and metaproteomics, will further elucidate the mechanism of interaction between the GM and the host, expanding it beyond bacterial taxonomy.…”
Section: Conclusion and Future Strategiesmentioning
confidence: 99%
“…Notably, it has been found that the metabolic profile in lungs from diseased patients, including lung cancer, significantly differs from that in healthy individuals (83)(84)(85). Notably some studies have found that specific metabolites are enriched in respiratory airways of patients with different diseases and this profile correlates with the presence of specific bacterial species (86)(87)(88).…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%
“…We successfully integrated the plasma and urine metabolomes with fecal microbiota data to interrogate changes in the microbiota-metabolome relationship that occur after toxic tall fescue exposure [ 69 ]. Within this study, the bidirectional relationship between the microbiota and metabolome [ 130 , 131 ], and how this shifts after placement on toxic versus non-toxic tall fescue pastures, was investigated. To do this, we used sparse partial least squares regression (sPLS) to integrate the datasets followed by a differential network analysis to reveal a highly correlated network of fecal OTUs and plasma/urine metabolites.…”
Section: The Case For Integrative Interactomics In Fescue Toxicosimentioning
confidence: 99%